Garlic bioactive substances and their therapeutic applications for improving human health: a comprehensive review - El-Saadony, Mohamed T.; Saad, Ahmed M.; Korma, Sameh A.; Salem, Heba M.; Abd El-Mageed, Taia A.; Alkafaas, Samar Sami; Elsalahaty, Mohamed I.; Elkafas, Sara Samy; Mosa, Walid F. A.; Ahmed, Ahmed Ezzat; Mathew, Betty T.; Albastaki, Noor A.; et al. (Frontiers in Immunology, 2024)
Garlic (Allium sativum L.) is a widely abundant spice, known for its aroma and pungent flavor. It contains several bioactive compounds and offers a wide range of health benefits to humans, including those pertaining to nutrition, physiology, and medicine. Therefore, garlic is considered as one of the most effective disease-preventive diets. Many in vitro and in vivo studies have reported the sulfur-containing compounds, allicin and ajoene, for their effective anticancer, anti-diabetic, anti-inflammatory, antioxidant, antimicrobial, immune-boosting, and cardioprotective properties. As a rich natural source of bioactive compounds, including polysaccharides, saponins, tannins, linalool, geraniol, phellandrene, β-phellandrene, ajoene, alliin, S-allyl-mercapto cysteine, and β-phellandrene, garlic has many therapeutic applications and may play a role in drug development against various human diseases. In this review, garlic and its major bioactive components along with their biological function and mechanisms of action for their role in disease prevention and therapy are discussed.